Pluck, not plunder - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Demand for medicinal plants is growing. But in the rush for quick profits, we may lose inestimable knowledge, much biodiversity and some common sense.Two in three people in developing countries use herbal medicine for their primary health care. Yet...